Handgrip strength and muscle fatigue among footwear industry workers - Lidiane Angélica Cotelez; Maysa Venturoso Gongora Buckeridge Serra; Eliane Ramos; José Eduardo Zaia; Flávia Oliveira Toledo; Paulo Roberto Veiga Quemelo
Abstract Introduction: Muscle fatigue can be defined as a decrease in the performance of the neuromuscular system in generating force. This situation is considered a complex physiological process involving various body systems, in order to avoid irreversible damage or even cell death. Objective: The aim of this study was to measure muscle strength in order to assess the level of fatigue among footwear industry workers, and to determine a possible correlation between muscle strength and the perception of reported fatigue. Materials and Methods: The study included 32 male workers from the footwear industry with a mean age of 34.63 ± 11.98 years. The workers performed the handgrip strength test using a handheld dynamometer, and completed the Bipolar Fatigue Questionnaire. Results: The mean result of strength testing was 23.1 ± 8.3 kgf, and the mean score of the fatigue questionnaire was 2.28 ± 0.93 points. However, a low correlation was observed between the results of the fatigue questionnaire and the strength test results. Conclusion: The grip strength results of the footwear workers were below the values for the general Brazilian population, a fact that may indicate potential muscle fatigue. However, a low correlation with the perception of fatigue was indicated by the questionnaire.